Kaidah ‘Aam, Khas dan Takhshish dalam Hukum Keluarga - Jannah, Fitri Miftahul; Ramadany, Tri; Azwar, Zainal (Akademika : Jurnal Keagamaan dan Pendidikan, 2023)
Pronunciation is an expression with which one thing can be understood. However, the meaning of the pronunciation will be greatly influenced by something that goes hand in hand with it. The meaning of lafaz can mean aam (general), special (special), and Takhsis. This paper will explore how lafaz can mean am, distinctive, and takhsis, accompanied by an explanation of the rules/provisions that can influence it. This study uses the library research method, where later the author will explain the discussion by including examples from the Koran and Hadith to find a clearer understanding of a syara' proposition. The results of this study found that there are three family laws that have gone through the stages of the takhshish rule, where the existing 'aam' pronunciation from the syara' proposition is taken so that the meaning becomes narrower or limited.